“Una inmensa cloaca de infección y de vicio”: Santiago popular y distopía en la historiografía y la novela chilena 1880-1900 - Araucaria Rojas Sotoconil (Les Cahiers ALHIM)
The main purpose of this text is to examine how popular Santiago is represented in Chilean historiography and novels produced between 1880 and 1900. In the first place, the aim is to answer the question of who inhabits the popular city, and then to investigate the dystopian description of the space. In both corpuses, particular attention is paid to the chingana, as the epitome of a bustling and unbridled town. It is also proposed that the characteristics attributed to the popular city are the same as those used to define the people: the territory embodies the excess and precariousness of those who inhabit it.